Gaku, Jutsu and Gei in Music Therapy - Murai, Yasuji (Voices: A World Forum for Music Therapy, 2001)
Needless to say, every therapist is trying hard to create his/her own professional personality in order to become a good therapist as a life long task. And the only premise for this task is to be a specialist of music therapy. However, aiming to be a good therapist varies depending on where each person puts his/her basis. For example, since my major work has been around schizophrenia, I have been trying to watch schizophrenic people closely and constantly. It might seem to be a natural task for a music therapist who deals with schizophrenia. But every time I have tried to summarize this disease, I have felt keenly how challenging this task is, even after a 30- year career. What on the earth is the cause of schizophrenia? It is said that the person's own make-up or hereditary predisposition might come into control, or the environmental factors might operate. But how do these things build up an individual to schizophrenia? How and when are the so-called "pre-personality tendencies" made, such as withdrawing or lack of self-confidence? This pattern of thoughts/behaviors that entice the person to the world of morbid experiences, has a close connection with the build-up of the disease. I personally believe that in this secret connection, there are some clues to the treatment. The work of discovering these clues is achieved by reviewing my own past clinical cases and other researchers' papers.